Recent Advances in Carbon Nanotube-Based Enzymatic Fuel Cells - Cosnier, Serge; Holzinger, Michael; Le Goff, Alan (Frontiers in Bioengineering and Biotechnology, 2014)
This review summarizes recent trends in the field of enzymatic fuel cells. Thanks to the high specificity of enzymes, biofuel cells can generate electrical energy by oxidation of a targeted fuel (sugars, alcohols or hydrogen) at the anode and reduction of oxidants (O2, H2O2) at the cathode in complex media. The combination of carbon nanotubes, enzymes and redox mediators was widely exploited to develop biofuel cells since the electrons, involved in the bio-electrocatalytic processes, can be efficiently transferred from or to an external circuit. Original approaches to construct electron transfer based CNT-bioelectrodes and impressive biofuel cell performances are reported as well as biomedical applications.